Exploring the potential utility of a wearable accelerometer for estimating impact forces in ballet dancers - Almonroeder, T. G.; Benson, L.; Madigan, A.; Everson, D.; Buzzard, C.; Cook, M.; Henriksen, B. (Journal of Sports Sciences, 2020)
Excessive forces and/or loading rates during landing may place ballet dancers at risk for overuse injury. The ability to estimate and monitor the landing forces of ballet dancers could help to improve injury prevention and rehabilitation; however, force platforms are not conducive to testing outside of a laboratory. Fortunately, it may be possible to indirectly assess landing forces via a wearable accelerometer. The purposes of this study were to examine the relationship between impact accelerations, recorded via a pelvis-worn accelerometer, and the peak forces and loading rates during performance of a common ballet manoeuvre, and to examine if a wearable accelerometer is sensitive to fatigue-related changes in landing forces. Fifteen ballet dancers continuously performed a ballet manoeuvre until self-determined exhaustion while impact accelerations and landing forces were simultaneously recorded using an accelerometer and force platforms. We observed very strong, positive relationships between the impact accelerations and the peak forces and loading rates during the landings. In addition, the changes in impact accelerations with fatigue paralleled the changes in the peak forces and loading rates. As a result, it appears that a wearable accelerometer could be used to estimate and monitor landing forces in ballet dancers.